Single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials and preparation methods and applications thereof
By using single-atom platinum-supported sea urchin-like nitrogen-doped molybdenum dioxide nanomaterial as an electrocatalyst in the electrochemical hydrogen evolution reaction, the problems of large ohmic losses when electrochemical decomposition of water to form hydrogen and high amount of platinum in precious metals are solved in the prior art, and a high efficiency and low energy consumption electrocatalytic reaction is achieved.
Patent Information
- Application Number
- CN202410704311.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-06-03
AI Technical Summary
The prior art has problems of large ohmic losses and slow electron transfer speed when electrochemically decomposing water to form hydrogen, and the precious metal platinum has high cost and low reserves, which limits its large-scale application.
The single-atom platinum-supported sea urchin-like nitrogen-doped molybdenum dioxide nanomaterial was used as an electrocatalyst, and the material was prepared by hydrothermal reaction and ammonia atmosphere heat treatment, reducing the amount of precious metals and improving catalytic activity and stability.
It has achieved the reduction of energy loss, increased reaction rate in electrochemical hydrogen evolution reaction, and significantly reduced the amount of precious metal platinum, with good electrocatalytic application prospects.
Smart Images

Figure CN118756197B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic materials, and relates to a nano hydrogen evolution electrode catalyst, a preparation method and an application thereof, and specifically relates to a single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial, a preparation method and an application thereof. Background Art
[0002] As a clean energy with high energy density, hydrogen is considered to be an ideal choice to replace traditional fossil fuels. Electrochemical decomposition of water to produce hydrogen and oxygen is an efficient, environmentally friendly and very attractive method. However, its large ohmic loss and slow electron transfer rate hinder its further commercial application. Therefore, in order to minimize energy loss while maintaining efficient energy conversion, active and stable electrocatalysts can be added to the electrodes of the water electrolyzer to increase the rate of the electrochemical reaction.
[0003] The noble metal platinum is considered to be a highly active catalyst for hydrogen evolution reaction, but the high cost and low reserves of platinum severely limit its large-scale application. In order to maintain high catalytic activity and high stability, the content of platinum must be strictly limited and reduced. The method of anchoring noble metal single atoms on catalyst supports to achieve the purpose of improving catalytic activity and stability has attracted increasing attention and provides an effective strategy for the development of cost-effective industrial catalysts. However, the properties of the support play an important role in determining the catalytic activity and stability of metal-supported catalysts. It is well known that abundant active centers, good electronic conduction and mass transfer properties, and long-term stability play a vital role in efficient electrocatalysts. Molybdenum dioxide (MoO2) is suitable as a supported catalyst because of its excellent metallic properties, strong corrosion resistance and high chemical stability. Therefore, combining a small amount of noble metals with suitable supports to form composite nanomaterials can not only reduce the cost of the catalyst, but also significantly improve the catalytic activity. For example, Zhou Weijia et al. proposed in Nano Energy 62 (2019) 127-135 that uniformly modifying platinum nanoclusters on hexagonal molybdenum dioxide ultra-thin nanosheets can form a highly efficient electrocatalyst that effectively catalyzes the hydrogen production reaction (HER) by electrolysis of water.
[0004] Patent CN113430568A discloses a platinum-loaded molybdenum dioxide hybrid nanomaterial, its preparation method and application in electrocatalysis, which reduces the use of precious metal Pt while improving the efficiency of hydrogen evolution catalytic reaction.
[0005] Patent CN108585044A discloses a method for preparing a cobalt-doped molybdenum dioxide nanopowder with a mylikes structure, and its application as a hydrogen evolution catalyst in water electrolysis, which avoids the addition of platinum elements while improving the efficiency of the hydrogen evolution reaction.
[0006] However, the existing technology faces problems such as complicated synthesis methods, relatively high platinum usage, and high overpotential of the hydrogen production reaction by electrolysis of water. Summary of the invention
[0007] In view of the above-mentioned prior art problems, the present invention provides a single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial and its preparation method and application. The single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial of the present invention is an electrochemical hydrogen evolution catalyst with high activity and high stability. While improving the performance of the catalyst, the amount of precious metal used is reduced, and it has good electrocatalytic application prospects. In order to achieve the purpose of the present invention, the technical scheme adopted is as follows:
[0008] On the one hand, the present invention provides a single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial and its preparation method and application, comprising the following steps.
[0009] S1. Preparing sea urchin-shaped molybdenum dioxide nanoparticles: mixing sodium molybdate dihydrate, water, ethylene glycol, and concentrated hydrochloric acid, and subjecting the resulting mixture to a hydrothermal reaction to obtain sea urchin-shaped molybdenum dioxide nanoparticles;
[0010] S2, preparing sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles: subjecting the sea urchin-shaped molybdenum dioxide nanoparticles obtained in step S1 to a heat treatment in an ammonia atmosphere to obtain sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles;
[0011] S3. Preparation of single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials: mixing the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles obtained in step S2 with water, ethylene glycol, and potassium chloroplatinate, reacting, and heat treating to obtain single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials.
[0012] The concentrated hydrochloric acid refers to commercially available concentrated hydrochloric acid with a mass percentage of hydrogen chloride of 36%-38%.
[0013] Preferably, in step S1, the volume ratio of water, ethylene glycol and concentrated hydrochloric acid is 300:4-6:1.
[0014] More preferably, and as a specific embodiment of the present invention, in step S1, the volume ratio of water, ethylene glycol and concentrated hydrochloric acid is 300:5:1.
[0015] Preferably, in step S1, the mixing is specifically stirring at room temperature for 2-4 hours.
[0016] More preferably, and as a specific embodiment of the present invention, the stirring is specifically stirring at room temperature for 3 hours.
[0017] Preferably, in step S1, the hydrothermal reaction is carried out at 160-180° C. for 15-20 hours.
[0018] As a specific embodiment of the present invention, in step S1, the temperature of the hydrothermal reaction is 160°C.
[0019] More preferably, in step S1, the temperature of the hydrothermal reaction is 170-180°C.
[0020] As a specific embodiment of the present invention, in step S1, the temperature of the hydrothermal reaction is 170°C.
[0021] More preferably, and as a specific embodiment of the present invention, in step S1, the temperature of the hydrothermal reaction is 180°C.
[0022] Preferably, in step S1, the hydrothermal reaction time is 15-20 hours.
[0023] More preferably, and as a specific embodiment of the present invention, in step S1, the hydrothermal reaction time is 16 hours.
[0024] Preferably, in step S1, after the hydrothermal reaction, the mixture is cooled, centrifuged, washed, and dried to obtain sea urchin-shaped molybdenum dioxide nanoparticles;
[0025] Preferably, in step S2, the ammonia atmosphere heat treatment has an ammonia concentration of 99.999% and a heating rate of 2°C / min.
[0026] Preferably, in step S2, the ammonia atmosphere heat treatment is performed at a temperature of 400-500°C.
[0027] As a specific embodiment of the present invention, in step S2, the ammonia atmosphere heat treatment is performed at a temperature of 400°C.
[0028] As a specific embodiment of the present invention, in step S2, the ammonia atmosphere heat treatment is performed at a temperature of 500°C.
[0029] More preferably, and as a specific embodiment of the present invention, in step S2, the ammonia atmosphere heat treatment is performed at a temperature of 450°C.
[0030] Preferably, in step S2, the heat treatment in an ammonia atmosphere takes place for 30-120 minutes.
[0031] As a specific embodiment of the present invention, in step S2, the ammonia atmosphere heat treatment is performed for 30 minutes.
[0032] As a specific embodiment of the present invention, in step S2, the ammonia atmosphere heat treatment is performed for 120 minutes.
[0033] More preferably, in step S2, the heat treatment in an ammonia atmosphere takes place for 60-120 minutes.
[0034] As a specific embodiment of the present invention, in step S2, the ammonia atmosphere heat treatment is performed for 60 minutes.
[0035] More preferably, and as a specific embodiment of the present invention, in step S2, the ammonia atmosphere heat treatment is performed for 90 minutes.
[0036] Preferably, in step S3, the chloroplatinic acid is an aqueous solution with a concentration of 0.1-3 mg / mL.
[0037] More preferably, and as a specific embodiment of the present invention, in step S3, the chloroplatinic acid concentration is an aqueous solution of 1.5066 mg / mL.
[0038] Wherein, in step S3, the volume of the chloroplatinic acid aqueous solution is 0.05-2.5 mL.
[0039] Preferably, in step S3, the volume of the chloroplatinic acid aqueous solution is 0.067-2 mL.
[0040] As a specific embodiment of the present invention, in step S3, the volume of the chloroplatinic acid aqueous solution is 0.067 mL.
[0041] As a specific embodiment of the present invention, in step S3, the volume of the chloroplatinic acid aqueous solution is 2 mL.
[0042] More preferably, in step S3, the volume of the chloroplatinic acid aqueous solution is 0.2-2 mL.
[0043] As a specific embodiment of the present invention, in step S3, the volume of the chloroplatinic acid aqueous solution is 0.33 mL.
[0044] As a specific embodiment of the present invention, in step S3, the volume of the chloroplatinic acid aqueous solution is 0.2 mL.
[0045] More preferably, in step S3, the volume of the chloroplatinic acid aqueous solution is 1-2 mL.
[0046] As a specific embodiment of the present invention, in step S3, the volume of the chloroplatinic acid aqueous solution is 1 mL.
[0047] Preferably, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.01-0.3.
[0048] As a specific embodiment of the present invention, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.01.
[0049] As a specific embodiment of the present invention, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.03.
[0050] As a specific embodiment of the present invention, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.3.
[0051] More preferably, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.05-0.3.
[0052] As a specific embodiment of the present invention, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.05.
[0053] More preferably, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.15-0.3.
[0054] As a specific embodiment of the present invention, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.15.
[0055] Further preferably, and as a specific embodiment of the present invention, in step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.225.
[0056] Preferably, in step S3, the volume ratio of water to ethylene glycol is 3-10:1.
[0057] More preferably, in step S3, the volume ratio of water to ethylene glycol is 4-9:1.
[0058] As a specific embodiment of the present invention, in step S3, the volume ratio of water to ethylene glycol is 4:1.
[0059] More preferably, and as a specific embodiment of the present invention, in step S3, the volume ratio of water to ethylene glycol is 9:1.
[0060] Preferably, in step S3, the reaction is specifically: reacting in a water bath at 50-70° C. for 10-12 h.
[0061] More preferably, and as a specific embodiment of the present invention, in step S3, the reaction is specifically: reacting in a water bath at 60° C. for 10 h.
[0062] Preferably, in step S3, after the reaction, centrifugation, washing and drying are performed.
[0063] Preferably, in step S3, the heat treatment is carried out in a 99.999% nitrogen atmosphere at a heating rate of 5°C / min.
[0064] Preferably, in step S3, the heat treatment temperature is 80-140°C.
[0065] As a specific embodiment of the present invention, in step S3, the heat treatment temperature is 80°C.
[0066] As a specific embodiment of the present invention, in step S3, the heat treatment temperature is 140°C.
[0067] As a specific embodiment of the present invention, in step S3, the heat treatment temperature is 120°C.
[0068] More preferably, in step S3, the heat treatment temperature is 80-100°C or 140°C
[0069] More preferably, and as a specific embodiment of the present invention, in step S3, the heat treatment temperature is 100°C.
[0070] Preferably, in step S3, the heat treatment time is 0.5-2h.
[0071] As a specific embodiment of the present invention, in step S3, the heat treatment time is 0.5h.
[0072] As a specific embodiment of the present invention, in step S3, the heat treatment time is 2 hours.
[0073] More preferably, and as a specific embodiment of the present invention, in step S3, the heat treatment time is 1 hour.
[0074] On the other hand, the present invention provides a single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial prepared by the above method.
[0075] In another aspect, the present invention also provides the use of the above-mentioned single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial in electrochemical catalytic water decomposition, comprising the following steps:
[0076] The nanomaterials are mixed with water, ethanol and Nafion solution, loaded on the base electrode as the working electrode; a three-electrode system is formed; the electrode is placed in an electrolyte with a voltage of -0.14~-0.8V.
[0077] Preferably, the concentration of the Nafion solution is 8%-15%.
[0078] More preferably, the concentration of the Nafion solution is 10%.
[0079] Preferably, the volume ratio of water, ethanol and Nafion solution is 75-85:5-15:5-15.
[0080] More preferably, the volume ratio of water, ethanol and Nafion solution is 80:10:10.
[0081] Preferably, the mass concentration of the nanomaterial in water, ethanol or Nafion solution is 1.5-2.5 mg / mL.
[0082] More preferably, the mass concentration of the nanomaterial in water, ethanol, or Nafion solution is 2 mg / mL.
[0083] Preferably, the base electrode comprises one of a nickel electrode and a carbon electrode.
[0084] More preferably, the base electrode is a nickel foam electrode.
[0085] Further preferably, the size of the nickel foam electrode is 0.5 cm×0.5 cm.
[0086] Preferably, the working electrode is dried.
[0087] Wherein, the three-electrode system consists of a working electrode, a reference electrode and a counter electrode.
[0088] Preferably, the reference electrode comprises one of a mercury / mercury oxide electrode and a silver / silver chloride electrode.
[0089] More preferably, the reference electrode is mercury / mercury oxide.
[0090] Preferably, the counter electrode comprises a platinum electrode or a grinding stone rod.
[0091] More preferably, the counter electrode is a platinum sheet electrode.
[0092] Preferably, the electrolyte includes one of sulfuric acid electrolyte and potassium hydroxide.
[0093] More preferably, the electrolyte is a sulfuric acid electrolyte.
[0094] Preferably, the electrolyte concentration is 0.1-1M.
[0095] More preferably, the electrolyte concentration is 0.5M.
[0096] Preferably, the voltage in the application is -0.14~-0.8V.
[0097] Wherein, in the application, the hydrogen evolution overpotential is less than 159 mV.
[0098] Preferably, in the application, the hydrogen evolution overpotential is ≤150 mV.
[0099] More preferably, in the application, the hydrogen evolution overpotential is ≤110 mV.
[0100] More preferably, in the application, the hydrogen evolution overpotential is ≤90 mV.
[0101] Further preferably, in the application, the hydrogen evolution overpotential is ≤66 mV.
[0102] As a specific embodiment of the present invention, in the application, the hydrogen evolution overpotential is 48 mV.
[0103] Compared with the prior art, the present invention has the following beneficial effects:
[0104] (1) The method for synthesizing single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials provided by the present invention is simple and easy to implement, and the synthesized sea urchin-shaped nanoparticles have good morphology and size uniformity.
[0105] (2) The single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial provided by the present invention can be used as an electrochemical hydrogen evolution catalyst with high activity and high stability. It reduces the amount of precious metals used while improving the catalyst performance, and has good prospects for electrocatalytic applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0106] Figure 1 These are structural characterization diagrams of the single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial (hereinafter referred to as sea urchin-shaped Pt@N-MoO2) nanoparticles prepared in Example 1, wherein a is the SEM image, b is the TEM image, c is the AC-HAADF-STEM image, d is the HRTEM image, e is the SAED image, and f is the EDS-mapping image of the four elements Mo, O, N, and Pt.
[0107] Figure 2 The SEM images of the sea urchin-shaped molybdenum dioxide nanoparticles (hereinafter referred to as sea urchin-shaped MoO2) prepared in Example 1 at different magnifications.
[0108] Figure 3 TEM images of the sea urchin-like MoO2 prepared in Example 1 at different magnifications.
[0109] Figure 4 The SEM images of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles (hereinafter referred to as sea urchin-shaped N-MoO2) prepared in Example 1 at different magnifications.
[0110] Figure 5 TEM images of the sea urchin-shaped N-MoO2 prepared in Example 1 at different magnifications.
[0111] Figure 6 SEM images of the platinum-loaded sea urchin-like molybdenum dioxide nanomaterial (hereinafter referred to as sea urchin-like Pt@MoO2) prepared in Comparative Example 2 at different magnifications.
[0112] Figure 7 TEM images of the sea urchin-shaped Pt@MoO2 prepared in Comparative Example 2 at different magnifications.
[0113] Figure 8 XRD diagrams of sea urchin-like MoO2, sea urchin-like N-MoO2 and sea urchin-like Pt@N-MoO2 prepared in Example 1, and sea urchin-like Pt@MoO2 prepared in Comparative Example 2; wherein the standard peaks below the diagram are cited from the standard card JCPDS-32-0671.
[0114] Fig. 9 FT-IR graphs of sea urchin-like MoO2, sea urchin-like N-MoO2, and sea urchin-like Pt@N-MoO2 prepared in Example 1, and sea urchin-like Pt@MoO2 prepared in Comparative Example 2.
[0115] Fig.10 This is the Mo 3d high-resolution XPS spectrum of the sea urchin-like MoO2 and sea urchin-like Pt@N-MoO2 prepared in Example 1.
[0116] Fig.11 High-resolution XPS spectra of Pt 4f of the sea urchin-shaped Pt@N-MoO2 prepared in Example 1 and the sea urchin-shaped Pt@MoO2 prepared in Comparative Example 2.
[0117] Fig.12 This is the N 1s high-resolution XPS spectrum of the sea urchin-shaped N-MoO2 and sea urchin-shaped Pt@N-MoO2 prepared in Example 1.
[0118] Fig.13 This is the XANES spectrum of Pt in the sea urchin-shaped Pt@N-MoO2 prepared in Example 1, wherein curve (1) represents the sea urchin-shaped Pt@N-MoO2, curve (2) represents the Pt single-element foil, and curve (3) represents platinum dioxide.
[0119] Fig.14 This is the extended X-ray adsorption fine spectrum of Pt of the sea urchin-shaped Pt@N-MoO2 prepared in Example 1, where curve (1) represents the sea urchin-shaped Pt@N-MoO2, curve (2) represents the Pt single-element foil, and curve (3) represents platinum dioxide.
[0120] Fig.15Polarization curves of sea urchin-like MoO2, sea urchin-like N-MoO2, sea urchin-like Pt@N-MoO2 prepared in Example 1 and sea urchin-like Pt@MoO2 prepared in Comparative Example 2, wherein the curves from left to right at the intersection with the dotted line are sea urchin-like MoO2 prepared in Example 1, sea urchin-like N-MoO2 prepared in Example 1, sea urchin-like Pt@MoO2 prepared in Comparative Example 2, and sea urchin-like Pt@N-MoO2 prepared in Example 1, respectively.
[0121] Fig.16 Figure 2 is the Tafel slope graph of the sea urchin-like MoO2, sea urchin-like N-MoO2, sea urchin-like Pt@N-MoO2 prepared in Example 1 and sea urchin-like Pt@MoO2 prepared in Comparative Example 2, wherein (1) represents the sea urchin-like MoO2 prepared in Example 1, (2) represents the sea urchin-like N-MoO2 prepared in Example 1, (3) represents the sea urchin-like Pt@MoO2 prepared in Comparative Example 2, and (4) represents the sea urchin-like Pt@N-MoO2 prepared in Example 1.
[0122] Fig.17 Nyguist diagrams of sea urchin-like MoO2, sea urchin-like N-MoO2, sea urchin-like Pt@N-MoO2 prepared in Example 1 and sea urchin-like Pt@MoO2 prepared in Comparative Example 2.
[0123] Fig.18 This is a stability test diagram of the chronopotentiometric response of the sea urchin-shaped Pt@N-MoO2 prepared in Example 1.
[0124] Fig.19 This is the in-situ XRD pattern of the sea urchin-shaped Pt@N-MoO2 described in Example 1.
[0125] Fig. 20 This is the in-situ Raman spectrum of the sea urchin-shaped Pt@N-MoO2 described in Example 1.
[0126] Fig.21 This is the SEM image of the sea urchin-shaped Pt@N-MoO2 prepared in Example 1 after being subjected to the HER activity test conditions described in the application example for 24 hours.
[0127] Fig. 22 This is the TEM image of the sea urchin-shaped Pt@N-MoO2 prepared in Example 1 after being tested for 24 hours under the HER activity conditions described in the application example.
[0128] Fig.23 This is the XRD pattern of the sea urchin-shaped Pt@N-MoO2 prepared in Example 1 after being tested for 24 hours under the HER activity conditions described in the application example, wherein the standard peaks below the figure are referenced from the standard card JCPDS-32-0671. DETAILED DESCRIPTION
[0129] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of protection claimed in this application, and those skilled in the art can make various changes and modifications to the invention of this application based on the disclosed content, which should also fall within the scope of protection claimed in this application.
[0130] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.
[0131] Some of the terms and definitions involved in the present invention are shown in Table 1:
[0132] Table 1
[0133]
[0134] The sources of raw materials in Table 2 below are for illustrative purposes:
[0135] Table 2
[0136]
[0137] Example 1
[0138] S1. Preparation of sea urchin-shaped molybdenum dioxide nanoparticles: 242 mg of sodium molybdate dihydrate was dispersed in 300 mL of water solvent, and 5 mL of ethylene glycol as a reducing agent and 1 mL of concentrated hydrochloric acid were added in sequence, and stirred at room temperature for 3 h. The mixed solution was then transferred to a 500 mL polytetrafluoroethylene-lined autoclave and subjected to a hydrothermal reaction at 180° C. for 16 h. After the reaction was completed, the autoclave was naturally cooled to room temperature, and a black solid was obtained by centrifugation, washing, and drying, which was sea urchin-shaped molybdenum dioxide nanoparticles (sea urchin-shaped MoO2).
[0139] S2. Preparation of sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles: placing the above sea urchin-shaped molybdenum dioxide nanoparticles in an atmosphere with an ammonia concentration of 99.999%, heating the mixture to 450°C at a heating rate of 2°C / min and calcining the mixture for 90 minutes to obtain sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles (sea urchin-shaped N-MoO2).
[0140] S3, take 100 mg of the above sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles, mix them with 9 mL of water and 1 mL of ethylene glycol, and then add a 1.5066 mg mL -11.5 mL of chloroplatinic acid solution was added and reacted in a water bath at 60°C for 12 h. The mixture was centrifuged and washed, dried in a vacuum environment at 60°C for 12 h, and then transferred to an atmosphere of 99.999% nitrogen. The temperature was increased to 100°C at a heating rate of 5°C / min and calcined for 1 h to obtain single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials (sea urchin-shaped Pt@N-MoO2).
[0141] Example 2
[0142] Compared with Example 1, in step S1, the hydrothermal reaction temperature is 170° C., and the rest are the same.
[0143] Example 3
[0144] Compared with Example 1, in step S1, the hydrothermal reaction temperature is 160° C., and the rest are the same.
[0145] Example 4
[0146] Compared with Example 1, in step S2, the temperature is raised to 400° C., and the rest are the same.
[0147] Example 5
[0148] Compared with Example 1, in step S2, the temperature is raised to 500° C., and the rest are the same.
[0149] Example 6
[0150] Compared with Example 1, in step S2, the calcination time is 30 min, and the rest are the same.
[0151] Example 7
[0152] Compared with Example 1, in step S2, the calcination time is 60 min, and the rest are the same.
[0153] Example 8
[0154] Compared with Example 1, in step S2, the calcination time is 120 min, and the rest are the same.
[0155] Example 9
[0156] Compared with Example 1, in step S3, 0.067 mL of chloroplatinic acid solution was added, and the rest was the same.
[0157] Example 10
[0158] Compared with Example 1, in step S3, a chloroplatinic acid solution with a mass fraction of 0.2 mL is added, and the rest is the same.
[0159] Embodiment 11
[0160] Compared with Example 1, in step S3, 0.33 mL of chloroplatinic acid solution is added, and the rest are the same.
[0161] Example 12
[0162] Compared with Example 1, in step S3, 1 mL of chloroplatinic acid solution is added, and the rest are the same.
[0163] Embodiment 13
[0164] Compared with Example 1, in step S3, 2 mL of chloroplatinic acid solution is added, and the rest are the same.
[0165] Embodiment 14
[0166] Compared with Example 1, in step S3, the heat treatment temperature is 80° C., and the rest are the same.
[0167] Embodiment 15
[0168] Compared with Example 1, in step S3, the heat treatment temperature is 120° C., and the rest are the same.
[0169] Example 16
[0170] Compared with Example 1, in step S3, the heat treatment temperature is 140° C., and the rest are the same.
[0171] Embodiment 17
[0172] Compared with Example 1, in step S3, the heat treatment time is 0.5 h, and the rest are the same.
[0173] Embodiment 18
[0174] Compared with Example 1, in step S3, the heat treatment time is 2 hours, and the rest are the same.
[0175] Embodiment 19
[0176] Compared with Example 1, in step S3, the volume of water is 8 mL, the volume of ethylene glycol is 2 mL, and the rest are the same.
[0177] Comparative Example 1
[0178] Compared with Example 1, in step S1, the hydrothermal reaction temperature is 200° C., and the rest are the same.
[0179] Comparative Example 2
[0180] Compared with Example 1, there is no step S3, and step S2 is changed to the following, and the rest are the same.
[0181] S2, platinum-loaded sea urchin-shaped molybdenum dioxide catalyst. 100 mg of the sea urchin-shaped molybdenum dioxide nanoparticles prepared in step S1 were dissolved in a mixed solution containing 9 mL of ethylene glycol and 1 mL of distilled water, and a concentration of 1.5066 mg mL -1 1.5 mL of H2PtCl6·6H2O solution was added. Next, the mixed solution was placed in a 60-degree water bath under magnetic stirring for 12 hours. After centrifugal washing, it was placed in a vacuum environment at 60°C and dried for 12 hours. Then, it was transferred to an atmosphere with a nitrogen concentration of 99.999%, heated to 100°C at a heating rate of 5°C / min and calcined for 1 hour to obtain platinum-loaded sea urchin-like molybdenum dioxide (Pt@MoO2) nanomaterials.
[0182] Application Examples
[0183] The single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials prepared in Examples 1-19 and Comparative Example 1 and the platinum-loaded sea urchin-shaped molybdenum dioxide nanomaterials prepared in Comparative Example 2 were respectively modified on the surface of the nickel foam electrode as electrocatalysts, and the HER activity of the prepared materials was electrochemically tested using an electrochemical workstation (CHI 760E, CH Instruments Ins., Shanghai, China). The specific process is as follows:
[0184] An impregnation solution with a nanomaterial concentration of 2 mg / mL was prepared, and the solvent was a mixture of 80% water, 10% ethanol, and 10% Nafion solution by volume. The impregnation solution was dripped onto a 0.5 cm × 0.5 cm nickel foam electrode, and after drying, it was used as a working electrode, a mercury / mercuric oxide electrode was used as a reference electrode, and a platinum sheet was used as a counter electrode to form a three-electrode system, and the catalytic activity of the electrocatalyst was tested in a 0.5 M sulfuric acid electrolyte.
[0185] The effects achieved by the above embodiments and comparative examples are shown in Table 3.
[0186] Table 3
[0187]
[0188] The following experiments further illustrate the effects achieved by the present invention.
[0189] Figure 1The SEM, TEM, HRTEM, AC-HAADF-STEM, SAED and EDS-Mapping images of the nitrogen-doped sea urchin-like molybdenum dioxide supported by single-atom platinum prepared in Example 1 are shown. The AC-HAADF-STEM image shows that Pt atoms are individually and evenly dispersed on the MoO2 surface as bright spots. In addition, very clear lattice fringes can be observed by HRTEM, indicating that the sea urchin-like Pt@N-MoO2 has a good crystal structure. The EDS-Mapping image also shows that Mo, O, N and Pt atoms are evenly dispersed throughout the sea urchin-like Pt@N-MoO2 sample. Figure 2-5 The TEM and SEM images of sea urchin-shaped MoO2 and sea urchin-shaped N-MoO2 at different magnifications show that the preparation process of nitrogen doping and platinum loading does not have a significant effect on the morphology and size of the nanomaterials. The TEM and SEM images of platinum-loaded sea urchin-shaped molybdenum dioxide nanoparticles prepared in Comparative Example 2 are shown in Figure 2. Figure 6 , 7 As shown in the figure, its microstructure is not much different from that of sea urchin-like Pt@N-MoO2. Figure 8 It can be seen that the crystal form of the four nanomaterials is monoclinic. Fig. 9 Figure 2 shows the FTIR spectra of the four nanomaterials. It can be seen that the vibration peak of the Mo=O bond in the sea urchin-like Pt@N-MoO2 is weak, which may be due to the bonding of Mo with Pt and N. Fig.10 The high-resolution XPS spectrum of Mo3d is shown, and we can see that Mo 4+ and Mo 6+ signal peak. Fig.11 This is the Pt 4f high-resolution XPS spectrum. It can be observed that Pt is mainly The XPS spectrum of N1s is as follows Fig.12 The signal peaks of pyridinic N, pyrrolic N and Mo 3p can be observed. This indicates that N doping is successfully incorporated into MoO2. Fig.13 The XANES spectrum of Pt in the urchin-like Pt@N-MoO2 is shown. The urchin-like Pt@N-MoO2 shows a higher white line intensity than that of platinum foil, but lower than that of PtO2, indicating that the Pt atoms are in a positively charged state in the urchin-like Pt@N-MoO2. The extended X-ray adsorption fine structure study examined the local coordination environment of the Pt atoms in the catalyst. Fig.14 The extended X-ray adsorption fine spectrum showed that Pt-O bonds existed in the sea urchin-like Pt@N-MoO2, but no Pt-Pt bonds were detected, confirming the single-atom dispersion state of the Pt species.
[0190] The sea urchin-shaped molybdenum dioxide nanoparticles, sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles, single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials prepared in Example 1, and platinum-loaded sea urchin-shaped molybdenum dioxide nanoparticles prepared in Comparative Example 2 were characterized for electrochemical catalytic activity using the method described in the application example. The results are as follows Figure 15-18 The specific analysis is as follows.
[0191] The linear sweep voltammetry (LSV) curve results are as follows: Fig.15 As shown, the scan rate is 5mV / s. The Tafel curve (b: Tafel slope, j: current density) is calculated according to the formula η=a+blog(abs(j)). The results are shown in Fig.16 Electrochemical impedance spectroscopy (EIS) was measured at -0.45 V for RHE, a low frequency of 0.1 Hz, and a high frequency of 10 6 The Nyguist diagram of the results is shown in Figure 1. Fig.17 Stability test as shown. Fig.18 shown.
[0192] Obviously, the platinum-loaded nitrogen-doped molybdenum dioxide hybrid nanomaterial prepared by the present invention has a good electrocatalytic hydrogen evolution effect under acidic conditions. 2 The overpotential is 48 mV at a current density of 1.3 % and the Tafel slope is as low as 47 mV / dec. -1 And it can maintain good stability within 24 hours. The Nyquist plots of several catalysts show that the charge transfer resistance (Rct) after doping has been effectively reduced, among which the Rct value of the nitrogen-doped molybdenum dioxide hybrid nanomaterial supported by platinum is much lower than that of bulk molybdenum dioxide, showing the lowest charge transfer resistance and the fastest charge transfer kinetics, indicating that the superior charge transfer kinetics is conducive to the rapid water electrolysis hydrogen production reaction (HER) process.
[0193] In-situ technology is conducive to in-depth analysis of the composition and structure of the catalyst. The stability of the urchin-shaped Pt@N-MoO2 catalyst prepared in Example 1 under different voltages in 0.5M H2SO4 was studied by in-situ X-ray diffractometer. Fig.19 As shown in Figure 1, the peak intensity of the main vibration peak at different voltages does not show significant changes during the electrocatalytic process, indicating that the composition of the material is stable during the catalytic process. In situ Raman spectroscopy was used to study the structural evolution of sea urchin-like Pt@N-MoO2 at different voltages in 0.5M H2SO4. The obtained 2D mapping image is shown in Figure 1. Fig. 20 As shown in Figure 2, no new characteristic peaks appeared during the electrocatalytic process, further proving that the urchin-like Pt@N-MoO2 has excellent durability. In order to further understand the stability of the urchin-like Pt@MoO2, the structure and surface chemical state after electrochemical testing were also studied. Figure 21-22 It is shown that the morphology and size of the urchin-like Pt@N-MoO2 do not change significantly after the HER reaction. Fig.23 The XRD pattern after HER shows that no additional crystalline phase is observed after the HER test, and the crystal structure remains unchanged, which further proves that the urchin-like Pt@N-MoO2 has good structural stability. Overall, a series of test results jointly prove the performance, structure and composition of the urchin-like Pt@N-MoO2 in acidic electrolytes.
[0194] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A method for preparing a single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial, characterized in that: The following steps are involved: S1. Preparing sea urchin-shaped molybdenum dioxide nanoparticles: mixing sodium molybdate dihydrate, water, ethylene glycol, and concentrated hydrochloric acid, and subjecting the resulting mixture to a hydrothermal reaction to obtain sea urchin-shaped molybdenum dioxide nanoparticles; S2, preparing sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles: subjecting the sea urchin-shaped molybdenum dioxide nanoparticles obtained in step S1 to a heat treatment in an ammonia atmosphere to obtain sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles; S3. Preparation of single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials: mixing the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles obtained in step S2 with water, ethylene glycol, and potassium chloroplatinate, reacting, and heat treating to obtain single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterials.
2. The preparation method according to claim 1, characterized in that: In step S1, the volume ratio of water, ethylene glycol and concentrated hydrochloric acid is 300:4-6:1, and the mixing is specifically stirred at room temperature for 2-4 hours.
3. The preparation method according to claim 1, characterized in that: In step S1, the hydrothermal reaction is carried out at 160-180° C. for 15-20 hours.
4. The preparation method according to claim 1, characterized in that: In step S2, the ammonia atmosphere heat treatment temperature is 400-500°C, and the heat treatment time is 30-120 minutes.
5. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the sea urchin-shaped nitrogen-doped molybdenum dioxide nanoparticles to potassium chloroplatinate is 10:0.01-0.
3.
6. The preparation method according to claim 1, characterized in that: In step S3, the volume ratio of water to ethylene glycol is 3-10:
1.
7. The preparation method according to claim 1, characterized in that: In step S3, the reaction is specifically: reacting in a water bath at 50-70°C for 10-12h.
8. The preparation method according to claim 1, characterized in that: In step S3, the heat treatment temperature is 80-140°C and the time is 0.5-2h.
9. Single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial prepared by the preparation method described in any one of claims 1 to 8.
10. Application of the single-atom platinum-loaded sea urchin-shaped nitrogen-doped molybdenum dioxide nanomaterial prepared by the preparation method according to any one of claims 1 to 8 in electrochemical catalytic water decomposition, characterized in that: The following steps are involved: The nanomaterials are mixed with water, ethanol and Nafion solution and loaded on the base electrode as the working electrode to form a three-electrode system; the electrodes are placed in an electrolyte with a voltage of -0.14~-0.8V to electrolyze water; Wherein, the three-electrode system consists of a working electrode, a reference electrode, and a counter electrode.
Citation Information
Patent Citations
Simple preparation and electrocatalytic application of Co-MoO2 nanosphere of mylikes structure
CN108585044A
Platinum-loaded molybdenum dioxide hybrid nano material and preparation method and electro-catalysis application thereof
CN113430568A